TAX CALCULATION OF GROUNDWATER EXTRACTION UNDER THE APPLICABLE LAWS OF UKRAINE AND REPUBLIC OF POLAND - Luibchyk О.; Koshliakov, O.; Kurilo, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The legal aspects, direct (administrative) and indirect (economic) instruments of state regulation of groundwater extraction were analyzed. According to the Ukrainian legislation, groundwater is in the Listed Minerals of national importance. The Water Code of Ukraine, the Code of Ukraine about subsoil and the Tax Code of Ukraine regulate the groundwater extraction and usage. At the same time In the Polish law the groundwater (except medical, brine and thermal) is not classified as mineral and is regulated by the Law of Water (Prawo wodne), the Law of Environmental Protection (Prawo ochrony środowiska) and the Law of Taxes on the income of financial entities (Ustawa o podatku Dochodowym od osib fizycznych). The structure of income generation of the subsoil owner was studied. According to the legislation of Ukraine it consists of the rent for the usage of mineral resources, the rent for the special usage of groundwater and the income tax. The Polish law determines only payment for the special usage of water and income tax. The scientific novelty consists in comparing the income generation of the subsoil owner in accordance to the legislation of Ukraine and Poland, determining its order in absolute values. It is stated that the structure of payments for the special usage of groundwater is significantly different. If the Ukrainian legislation of the tax rate depends on the administrative position of the object, the Polish legislation depends on the type of water consumption and the method of purification. The practical value of the research is in the application of results to improve system of state regulation of groundwater extraction through indirect (economic) instruments: implementation of payments differentiation with regard to the conditions of groundwater, quality, aquifer depth and type of water usage.